Strategies for sustainable access to electronic resources during COVID-19 pandemic: Experience from the Consortium of Uganda University Libraries (CUUL) (KLISC Journal of Information Science & Knowledge Management, 2024)
The paper shares the strategies the Consortium of Uganda University Libraries (CUUL) adopted to provide access to electronic resources to its member libraries in COVID-19 pandemic era. It examines the challenges, opportunities COVID-19 brought and how CUUL managed to deliver its mandate during the pandemic. The study used a qualitative research approach and a survey research design. A structured online interview data collection tool was employed to collect the required information from the CUUL executive committee members and the electronic resources functional committee. Content analysis method, with coding and categorization, was used for data analysis and presentation of findings. This paper creates awareness of the challenges, opportunities COVID-19 brought and strategies the CUUL used to sustain e-resources subscription since the outbreak of COVID-19. Funding and licensing costs are among the challenges mentioned while the opportunities were that the funders’ awareness of the need for e-resources and the online learning needs justified the need for e-resources sustainability by the consortium. Embracing open access initiatives, remote access and longer licensing period were among the strategies for e-resources sustainability. This paper provides effects and strategies for responding to global hazards that have the potential to affect consortium’s income for sustainable subscription to e-resources. It also adds literature on the impact of COVID-19 on university libraries in developing countries which is minimal.